New hybrid kenaf fibre/epoxy reinforced aluminium laminate composite for structural application - Osman, Edynoor (2019)
Fibre metal laminates (FML) technology is an effective way to increase the range of application of kenaf fibre composite in industries and offers some superior mechanical properties. The drawback of kenaf fibre composite is a low strength, high water absorption and the effect of thermal has become a big issue especially for the structural application. Also, lackingof data publish especially in FML technology involving kenaf fibre and increasing environmental concerns cause this study is vital to be explored. The present study is carried out the fabrication of kenaf fibre reinforced aluminium laminatescomposites (KeRALL) for structural application. It includes a comparison of KeRALL fabrication methods, the effect of pre-treatment of kenaf fibers and Al sheets as well as the effect of hygrothermal on KeRALL performance. The methodology was divided into 3 experiments, namely KeRALL fabrication through cold compression (CC) at 27 °C and warm compression (WC) at 80 °C, chemical (kenaf) and mechanical (Al) treatment processes and hygrothermal effects at 30, 60 and 80 °C. Innitially, thermal analysis by DSC showed a better curing degree of epoxy resin in WC as compared to CC. While, dynamic mechanical analysis (DMA) demonstrated that Tg was extended to 100–150 oC for CC as compared to 50–100 oC for WC. Thermal expansion result showed coefficient of thermal expansion of KeRALL WC almost matched that of Al sheet with only 21% differences. This explained the significant improvement of flexural strength and water resistance in KeRALL WC. It showed the highest flexural strength and lowest water absorption of KeRALL WC, 296.10 MPa and 7.9 %, respectively. Fractographic images illustrated a good interfacial bonding of KeRALL that prepared by WC. For the pre-treatment effect, the flexural test results showed that the KeRALL WC with surface roughened aluminum sheets gave higher values of increment, 283%. However, KeRALL WC with alodine treated aluminum showed the highest impact strength, 37.99 MPa contributed by interfacial delamination as a result of less firm adhesion between Al sheet and composite core. The KeRALL WC also showed improvement in water resistance at less than 9% as compared to the kenaf fibre reinforced composite (KFRC) at about 19%. For hygrothermal effect, KeRALL WC immersed at 30 °C shows the lowest water absorption rate, 4.7%. Mechanical properties of KeRALL shows an overall decreasing trend with the increase of immersion temperature. At 30 °C, 7 % decrement of interlaminar shear stress (ILSS) were recorded, followed by 66 % at 60 °C and 54 % at 80 °C. The significant finding of KeRALL is similar toSiRAL density about 23% increase as well as a high increment of flexural strength about more than 280% compared to kenaf fibre reinforced composite and thus has potential to be commercialized in the structural applications.